Expression of p53, bax and bcl-2 and Predictive Value of Fibrinogen, D-Dimer, and Mean Platelet Volume in Patients with Acute Cerebral Infarction after Intravenous Thrombolysis: Gene expression and FIB, D-D and MPV in Patients with ACI - Xu, Yuanfeng; Wang, Jiajia; Mao, Lunlin; Ji, Lili; Chen, Wenya (Cellular and Molecular Biology, 2022)
This was to study the application value of fibrinogen (FIB), D-dimer (D-D), and mean platelet volume (MPV) in the prediction of vascular re-occlusion (VRO) after intravenous thrombolysis (IVT) in patients with acute cerebral infarction (ACI). 114 patients with ACI were retrospectively included as the research objects and then were divided into the improvement group (66 cases) and the progressive group (48 cases). A multivariate Logistic regression model was applied to analyze the independent risk factors of VRO after IVT. The receiver operator characteristic (ROC) curve was also adopted to assess the predictive value of relevant factors for VRO after IVT. In addition, the expression of p53, bax and bcl-2 genes was investigated in patients with acute cerebral infarction and healthy people by real-time PCR. As a result, MPV, FIB, and D-D levels of venous blood in the improvement group were remarkably lower than those in the progressive group (P<0.05). The regression coefficients between MPV, FIB, D-D at admission and VRO after IVT were 0.411, 0.362, and 0.391, respectively, so there was a significant positive correlation (P<0.05). The combined prediction model of MPV, FIB, and D-D had greater sensitivity, specificity, and area under the curve (AUC) in predicting the risk of VRO after IVT than single MPV, FIB, or D-D, showing differences of statistical significance (P<0.05). In conclusion, MPV, FIB, and D-D in venous blood at admission were independent risk factors for the VRO after IVT. The combined model of MPV, FIB, and D-D had an excellent predictive performance on the risk of VRO after IVT. The expression level of genes p53 and bax was 4.5 and 3 times higher in patients than in controls, respectively. The expression of gene bcl-2 decreased (0.75 times) in patients (P<0.001).